Anchor Investors: Igniting or Extinguishing the Fire? - Sharma, Akanksha; Kumar, Santosh (Indian Journal of Finance, 2012)
SEBI brought a significant amendment in 2009 by introducing the concept of Anchor Investors in its Disclosure and Investor Protection (DIP) Guidelines 2000 to ensure higher efficiency in the Indian stock market. An Anchor Investor is a Qualified Institutional Buyer (QIB), who can invest up to 30% of the QIB quota, subject to a minimum corpus of ` 10 crores as investment, and a lock-in period of at least 30 days. This measure was introduced to protect shareholder wealth during market volatility such that big institutional investors do not sell off their shares as soon as they foresee a plunging market. This paper, therefore, using the data for 17 of the IPOs issued between July 2009 and March 2011, attempts to find whether this directive by SEBI actually served its purpose of boosting investor confidence and providing stability in a volatile market. Whilst this was a welcome step, our results indicate that anchor investors neither guarantee share price stability, nor incite investors to follow their lead as they enter and exit the fund in spite of substantial subscription in the IPO. Our findings are in congruence with Mathur and Subramaniam (2011), Venkatraman and Khemka (2010), and Ram (2009).